The Influence of Regional Expenditure In The Education, Health, And Investment Sectors On The Human Development Index In Eastern Indonesia Region - Nilam Nofiana Erwanti; Wahyunadi Wahyunadi; Hadi Mahmudi (Return : Study of Management, Economic and Bussines, 2023)
This study aims to analyze the effect of Regional Expenditure on Education and Health derived from the  APBN and APBD, Domestic Investment, and Foreign Investment on the Human Development Index in Eastern Indonesia. This study uses the panel data analysis method. The research data use time series data from the 2015-2019 period and cross-section data on 13 provinces in Eastern Indonesia. The variables used in this study are the HDI as the dependent variable, then the Education and Health Deconcentration funds, Education and Health Function Expenditures, DDI and FDI Investment Realization as independent variables. The results showed that regional expenditure in the field of education originating from the APBN had a significant negative effect on HDI in Eastern Indonesia, regional expenditure in the field of education originating from the APBD had a significant positive effect on HDI, regional expenditure in the field of health originating from the APBN had a negative and insignificant effect on HDI, regional expenditure in the field of health originating from the APBD had a significant positive effect on HDI. DDI has a positive and insignificant effect on HDI. FDI partially has a negative and insignificant effect on HDI